Virulence Factors and Antibiotic Resistance of Klebsiella pneumoniae Strains Isolated From Neonates With Sepsis - Khaertynov, Khalit S.; Anokhin, Vladimir A.; Rizvanov, Albert A.; Davidyuk, Yuriy N.; Semyenova, Dina R.; Lubin, Sergey A.; Skvortsova, Natalia N. (Frontiers in Medicine, 2018)
Introduction. Klebsiella pneumoniae is one of the most important infectious agents in neonates. There are "classic" and hypervirulent strains of K. pneumoniae. The “classic” strain of K. pneumoniae is associated with nosocomial infections. The role of virulent strains of K. pneumoniae in neonatal infections is unknown. The aim of the study was the assessment of the impact of virulence factors and antibiotic resistance of K. pneumoniae strains on clinical features and outcomes of neonatal infection. Material and methods. Two groups of infants were enrolled. The first group consisted of 10 neonates with sepsis caused by K.pneumoniae. The second group consisted of 10 neonates with urinary tract infection (UTI) caused by K.pneumoniae. We investigated the susceptibility of K.pneumoniae isolates to antibiotics, the ability of the microorganism to produce ESBL, and virulence factors, including the rmpA gene, aerobactin ,and colibactin genes. In neonates with sepsis, we investigated K.pneumoniae isolates, which was taken from the blood, in neonates with UTI – from the urine. Results. In neonates with sepsis testing of K. pneumoniae isolates for ESBL production was positive in 60% of cases, in neonates with UTI – in 40% of cases. All blood and urine ESBL producing K. pneumoniae isolates were resistant to ampicillins, including protected ones, and third-generation cephalosporins. At the same time, these isolates were sensitive to meropenem, amikacin ,and ciprofloxacin. The rmpA gene was detected in four blood, and three urine K.pneumoniae isolates. In neonates with sepsis rmpA gene in two cases was detected in ESBL-producing K.pneumoniae isolates. They were infants with meningitis ,and both cases were fatal. In the group of infants with UTI, the rmpA gene was detected only in K. pneumoniae isolates not producing ESBL. Aerobactin and colibactin genes were detected in two neonates with sepsis and in three neonates with UTI. In all cases, aerobactin and colibactin genes were detected only in rmpA-positive K. pneumoniae isolates. Out of three fatal outcomes, two cases were caused by hv-KP producing ESBL. Conclusion. The most severe forms of neonatal sepsis with an unfavorable outcome in our study were due to virulent strains of K. pneumoniae.